Tujuan Disertakannya Nama Perempuan dalam Silsilah Yesus Berdasarkan Injil Matius 1:1-17 - Theresia Endang Sulistyawati (STT Injili Indonesia Medan, 2020)
This paper aims to explain the genealogy of the birth of Jesus Christ in the gospel of Matthew 1:1-17 which writes about foreign women and explain why Jesus also comes from the descendants of his father and his mother's. For Christians Mary is a holy virgin from the tribe of Jehuda. Jehuda the son of the king of David and ancestor of Jesus Christ humanly. The method used is text analysis with literature review. From the analysis, it can be concluded that the inclusion of the list name of foreign women Matthew wants to make clear that God's work of salvation cannot be limited by human sin. God can use sinners to complete His work of salvation.